Mapping survey of schistosomiasis and soil-transmitted helminthiases towards mass drug administration in The Gambia. - Yaya Camara; Bakary Sanneh; Ebrima Joof; Abdoulie M Sanyang; Sana M Sambou; Alhagie Papa Sey; Fatou O Sowe; Amadou Woury Jallow; Balla Jatta; Sharmila Lareef-Jah; Sainey Sanneh; Flobert Njiokou; et al. (PLoS Neglected Tropical Diseases)
Background A national mapping survey of schistosomiasis (SCH) and soil-transmitted helminthiases (STH) was conducted in The Gambia in May, 2015. The survey aimed at establishing endemicity of schistosomiasis and soil-transmitted helminthiases to inform decisions on program planning and implementation of mass drug administration (MDA). Methodology/principal findings A cross-section of 10,434 eligible school aged children (SAC), aged 7 to 14 years old were enrolled in the survey. The participants were randomly sampled from 209 schools countrywide using N/50, where N = total eligible children per school. Stool, and urine samples were provided by each child and examined for schistosomiasis and soil-transmitted helminthic infections using double Kato-Katz, urine filtration, dipstick techniques and CCA rapid test kits. Data were managed using online LINKS system enabling real-time data availability and access. Epi Info version 3.5.3 and health mapper version 4.3.2 were used to generate outputs of endemicity and distribution. Descriptions of mapped districts for MDA eligibility and frequency were done with reference to WHO PC strategy recommendations. Mapping results indicated that nationally, the prevalence of schistosomiasis (SCH) and soil-transmitted helminthiases (STH) was 4.3% and 2.5% respectively. In terms of distribution STH are more common in Western Region One (WR1) at 4.1% prevalence, then Lower River Region (LRR) 3.6%, and Western Region Two (WR2) 3.0%. In contrast, SCH indicated much higher prevalence in Central River Region (CRR) at a rate of 14.2%. This is within medium prevalence range, and is followed by Upper River Region (URR) at 9.4%, which is within low prevalence range. At the district level, schistosomiasis prevalence seems to be highest in Niani district (22%) in CRR. Banjul island, the capital city, seems to have the highest prevalence of STH (up to 55%), followed by Kombo South with 22% prevalence. Schistosoma haematobium characterised by haematuria, was the most dominant infection of schistosomiasis discovered followed by Schistosoma mansoni which reported in 0.1% of infections. Out of 42 districts mapped 14, or 38%, of them are co-endemic for soil-transmitted helminthiases (ascariasis, trichuriasis, and hook-worm infections) and schistosomiasis (S. haematobium and S. mansoni). Conclusions We identified that 24/42(57%) districts mapped in The Gambia are endemic for schistosomiasis expressing the need for preventive chemotherapy. Twenty (47%) of the districts mapped are endemic for STH. However, only two STH endemic districts namely Banjul (55%) and Kombo South (22%) were within rates eligible for mass drug administration.